La Expresión Corporal como Herramienta en el Desarrollo de la Conciencia Corporal, Cuerpo y Movimiento, en los estudiantes del curso 3ª del colegio Colombo Florida Bilingüe (2017)
The movements and the different possibilities that the human body has to communicate and express themselves in less than a second must be developed from the first years of life. The Body Expression as an element of communication between man and movement, serves as a tool in the acquisition and development of body awareness, since it works from the "union of three fundamental areas" (physical-psychological-social), and in turn it serves us to transmit thoughts, feelings, emotions, moods and sensations, through body language.